HUBUNGAN KETEPATAN TERAPI OBAT ANTIDIABETIK ORAL DENGAN NILAI HBA1C PADA PASIEN DIABETES MELITUS TIPE 2 PROLANIS DI PUSKESMAS JATILAWANG - Ika Yuliani; Luthfi Hidayat Maulana; Teguh Hary Kartono (Jurnal Farmasi Universitas Peradaban, 2021)
Diabetes mellitus (DM) is a metabolic disease that has hyperglycemia characteristics caused by abnormalities in insulin secretion, insulin action or both. This research aims to find out the relationship between the accuracy of therapy in patients with type 2 diabetes mellitus in Prolanis in Jatilawang Public Health Center, Banyumas Regency. medical records of patients with type 2 diabetes mellitus The results show that of 41 patients with type 2 diabetes mellitus in the jatilawang puskesmas banyumas district are aged 40-60 years as many as 23 or 56.1%, and aged 61-80 years as many as 18 or (43,996) . Type 2 Diabetes Mellitus patients consisted of 3 male patients (7.3%) and 38 female patients (92.7%), with 18 (46,316) cases of patients with housewives as many as 25 or (61.06) and frequency of work the least is the work of traders and tailors of clothes by 1 patient or 2.4%. Based on the level of education having the most education, namely elementary schools as many as 31 or (75.6%) and the least frequency has D2 education of 1 or 24%. Based on the length of time involved in being a prolanist participant, the highest frequency of prolanis Diabetes Mellitus type 2 patients at the Jatilawang Public Health Center in Banyumas Regency was based on the time of 34 years of 19 patients or (46.3%) and at least 6 patients or (14.6%) with 1-2 years in attendance. Type 2 diabetes mellitus without comorbidities and 22 (53.7%) cases of type 2 diabetes mellitus patients with hypertension. This research uses analytical observational method with sectional crots design. The accuracy of patient therapy results is that the patient who has the right indication is 41 patients (100.0%), the right drug selection is 41 patients (100%), the right dose is 41 patients (100.0%). right patient as many as 40 patients (100%), while for the right way to use as many as 24 patients or 58.5% Hbale value was reached as many as 28 patients or 68.33% and the target patient was not achieved as many as 13 patients or (31.7%). The results were analyzed using spas using Chi-square test The P value of 0.014 indicates that there is a relationship between the accuracy of therapy with the HbAle value in prolanis patients at the Jatilawang Public Health Center in Banyumas district